Mammography decision making: Trends and predictors of provider communication in the Health Information National Trends Survey, 2011 to 2014. Issue 3 (11th October 2016) - Spring, Laura M.; Marshall, Megan R.; Warner, Erica T.
Abstract : BACKGROUND: In 2009, the US Preventive Services Task Force recommended that the decision to initiate screening mammography before age 50 years should be individualized. Herein, the authors examined whether health care providers are communicating regarding mammography decision making with women and whether communication is associated with screening behavior. METHODS: Data were drawn from the 2011 to 2014 Health Information National Trends Survey (HINTS). A total of 5915 female respondents aged ≥ 40 years who responded to the following question were included: "Has a doctor or other health professional ever told you that you could choose whether or not to have a mammogram?" We used logistic regression to generate odds ratios (ORs) and 95% confidence intervals (95% CIs) for predictors of provider communication and assessed whether provider communication was associated with mammography in the previous 2 years overall and stratified by age. RESULTS: Fewer than 50% of the women reported provider communication regarding mammogram choice. Women who reported provider communication were not found to be more likely to report no mammogram within the past 2 years (OR, 1.07; 95% CI, 0.87‐1.31) compared with those who did not. When stratified by 10‐year age group, provider communication was associated with a higher likelihood of no mammogram only among women age ≥70 years (OR, 1.64; 95% CI, 1.15‐2.34), and was associated with a lower likelihood of no mammogram only among women aged 40 to 49 years (OR, 0.63; 95% CI, 0.43‐0.92). CONCLUSIONS: Between 2011 and 2014, less than one‐half of women received communication regarding mammogram choice despite recommendations from the US Preventive Services Task Force. Provider communication regarding mammogram choice can influence screening behavior, particularly for younger and older women. Cancer 2017;123:401–409. © 2016 American Cancer Society . Abstract : From 2011 to 2014, fewer than one‐half of women received provider communication regarding mammogram choice in the study population, despite the recommendations of the US Preventive Services Task Force. Provider communication concerning mammogram choice can influence screening behavior, particularly for women aged 40 to 49 years and those aged ≥70 years.